Exploring the Integration-Interconnection Paradigm in the Indonesian Context of Community Education And Practice - Muchammadun Muchammadun (Ulumuna, 2020)
The paper explores the daunting question as to how the integration-interconnection paradigm is actualised in the context of academic disciplines in Indonesia. This is accomplished by specifically analysing its application, through a purposive sampling of previously published studies, to the field of community development. The subsequent conclusions reveal core features of the integration-interconnection paradigm and its historical roots, and their relevance for community education and development today. In supporting the integration-interconnection paradigm, the writer proposes that Rothman’s and Ann Jeffries’ revised community development model is suitable for modification to accommodate local community education and practice in Indonesia. The paper identifies three major findings from studies in this field and discusses their implications. Firstly, from the epistemological point of view, there is a growing belief that science and religion are able to engage in collaborative dialogue rather than exist in mutual isolation. This will ensure an enhanced understanding of human interaction within our social environment. Secondly, religion and spirituality may potentially contribute to establishing a shared-base for supporting ethical values for professional practice. The final finding is that community developers, working from these underpinning assumptions, are more likely to succeed in their goals through exploring participatory ways of community practice.